Cork Oak Vegetation Series of Southwestern Iberian Peninsula: Diversity and Ecosystem Services - Quinto-Canas, Ricardo (2022)
Currently, the occurrence of thermophile cork oak communities is becoming exceptionally rare, which can be attributed to the long-lasting impact of human agroforestry and grazing land-use practices. In this work we identified the thermophilous cork oak vegetation series of southwestern of the Iberian Peninsula and present an overview of ecologic factors and processes controlling the diversity of plant communities observed in their dynamic, as well as, the characteristic vascular flora, including species with special conservation interest, is here presented. This information allows the development of sustainable management, which may enhance both biodiversity and conservation. Moreover, the sustainable economic activities of the cork oak forests, regarding to enhance their capacity to provide benefits that are essential for ecosystem services is developed and presented.